The specificity of regulatory protectionism in contemporary foreign trade policy - Puślecki, Zdzisław W. (Research Papers of Wrocław University of Economics, 2018)
In this research work, the author focuses on the analysis of the problem of specificity the regulatory protectionism in contemporary foreign trade policy. It has been emphasized that the talks between EU and USA will make reducing regulatory barriers. New agreements to remove trade barriers aim at reducing dead-weight costs and at increasing net social gains from international trade. The article examined the impact of investor-state dispute resolution mechanisms in reducing the power of national governments to regulate and elimination of market inequality. The article offers examples of successful regulatory cooperation efforts in the hope that it will shed light on possible approaches to addressing regulatory divergences. Ideally, the best way to address problems arising from regulatory divergence would be on a multilateral basis. The main aim of the article is the presentation of the specificity of the regulatory protectionism in contemporary foreign trade policy
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2018; Nr 509, s. 354-372
Keywords: foreign trade policy; regulatory protectionism; reducing; regulatory divergence; harmonization; mutual negotiation; zagraniczna polityka handlowa; protekcjonizm regulacyjny; redukcja; zróżnicowania regulacyjne; harmonizacja; wzajemne uznawanie